2018
DOI: 10.1002/gj.3238
|View full text |Cite
|
Sign up to set email alerts
|

Selenium and tellurium concentrations of Carboniferous British coals

Abstract: Standard mode and collision/reaction cell mass spectroscopy methods have been utilized in order to overcome spectral interferences and provide ultra‐low quantification of selenium (Se) and tellurium (Te) in British Carboniferous coals for the first time. The accurate detection of Se and Te in coals is becoming increasingly important, as coals and pyrite have been identified as potentially significant trace element sources. The mean Se concentration of British coals bear comparison to that of world coals, with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Minerals 2020, 10, x FOR PEER REVIEW 2 of 15 (5) The context of trace element sulphur in the gold is variable, suggesting that it is a natural precipitate rather than a man-made artefact. Bulk ICP-MS analysis of the coal shows a mean selenium content of 9.7 ppm (n = 9; Table 1), higher than the mean selenium content of British coals (2.1 ppm; [44]). Samples generally free of visible pyrite and siderite (CC1-CC2) contain 0.7 to 0.8 ppm selenium, while pyritic coal samples contain 4.2 to 7.1 ppm selenium and heavily pyritic-sideritic coal samples contain up to 25.8 ppm selenium.…”
Section: Resultsmentioning
confidence: 82%
“…Minerals 2020, 10, x FOR PEER REVIEW 2 of 15 (5) The context of trace element sulphur in the gold is variable, suggesting that it is a natural precipitate rather than a man-made artefact. Bulk ICP-MS analysis of the coal shows a mean selenium content of 9.7 ppm (n = 9; Table 1), higher than the mean selenium content of British coals (2.1 ppm; [44]). Samples generally free of visible pyrite and siderite (CC1-CC2) contain 0.7 to 0.8 ppm selenium, while pyritic coal samples contain 4.2 to 7.1 ppm selenium and heavily pyritic-sideritic coal samples contain up to 25.8 ppm selenium.…”
Section: Resultsmentioning
confidence: 82%
“…In addition to providing a frame of reference for thermal maturity in sedimentary sections of Carboniferous age, the database of vitrinite reflectance has applications for diverse purposes that involve national surveys. For example, the data can be used in assessments of coal bed methane (DECC 2013), shale gas potential (Smith et al 2011), geothermal energy (Gluyas et al 2018) and the interpretation of trace element data in coals (Bullock et al 2018 Lat., latitude; Long., longitude; R 0 , mean vitrinite reflectance; n, number of analyses; Inferred Fm, inferred host formation; CM, Coal Measures (Upper, Middle, Lower); WG, Warwickshire Group; CG, Clackmannan Group; LCG, Limestone Coal Group; LCF, Lower Limestone Formation; YG, Yoredale Group; n.g., number of analyses not given or not deciphered from source. Depths given estimated based on seam stratigraphy, shaft excavation depth or borehole data (where available).…”
Section: Discussionmentioning
confidence: 99%
“…Bullock et al 93 found Te enrichment at the pyrite rim of the coal using LA-ICP-MS techniques. In addition, Bullock et al 94 indicated that the average concentration of Te is associated with early syngenetic and later cleat-filling pyrite by investigating British Carboniferous coals. closely associated, which is to be expected for these siderophile elements.…”
Section: Acsmentioning
confidence: 99%